Persepsi, Pengetahuan, dan Sikap tentang Obat pada Siswa Sekolah Menengah Atas (SMA) di Kota Pariaman, Sumatera Barat - Syofyan Syofyan; Habibie Deswilyaz Ghiffari; Erizal Zaini (Jurnal Sains Farmasi & Klinis, 2017)
The irrational use of drug and drug abuse are some of the impacts of low public knowledge about medicine, including in high school students. The purpose of this study was to assess perceptions, knowledge and attitudes about medicine among senior high school students in Pariaman City, West Sumatera. The research was conducted by descriptive and analytical method with cross-sectional by using questionnaire instrument. Data were analyzed using univariate and bivariate analysis. The results showed that students’ perception on medicine was categorized as high (95.5%), student attitude was positive (60.3%) but had less knowledge (74.8%). Students living in the city had higher knowledge than those living in the village. There was a significant correlation between perception and attitude (P <0.05), however, there was no correlation between knowledge and perception level (P> 0.05) and attitude (P> 0.05). Low perceptions and knowledge can encourage students to do more fatal errors such as medications or irrational drug use. Efforts such as education about medication in schools are very important steps to improve students’ knowledge about medicine.